Hubungan antara Kemampuan Matematika dengan Keterampilan Pemrograman - Zulkipli, Zulkipli (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2023)
The development of computers lasted for five generations, starting from 1940 until now. Along with rapid technological developments, software innovations in certain fields must be carried out to facilitate data processing. There is a phenomenon where some Informatics Students question